Rat Kidney Cancers Determined by Dietary Ochratoxin A in the First Year of Life - Peter George Mantle (Journal of Kidney Cancer and VHL, 2016)
An experiment to explore renal carcinogenic efficacy of male rat exposure to dietary ochratoxin A (OTA) only in the first year of life has been made in comparison to lifetime exposure. Ten months exposure to OTA at 300 μg/kg b.w. was sufficient to cause high incidence of tumours which became apparent clinically after a latency of up to a year. As a putative model for human kidney cancer, the study shows a silent organ-specific carcinogenic effect through protracted exposure up to middle age and focused probably on very few nephrons. So far, tumourigenesis has not been recognised until in the last quarter of natural rat life, but for OTA, rat renal carcinogenesis requires both long exposure and only during the first year of normal longevity. The present findings offer an experimental framework within which systematic histopathology during tumourigenesis might show whether findings of mechanistic studies in key focal neoplasms can reasonably be applied to OTA as a putative renal carcinogen for idiopathic kidney cancer in humans. Already, the rat tumours mimic those occurring spontaneously in the Eker rat, and there is disparity between the large necessary OTA exposure in the rat and the trace amounts of OTA consumed by humans. In all such complex considerations it is important to adhere rigorously to established principles of disease epidemiology. Supplementary Figure: The supplementary figure of this article is found under 'Article Tools' at the left side bar.